En studie om sambandet mellan priselasticitet och konsumenters lojalitet för livsmedel i Sverige - Oxwall,Axel; Karcic,Lejla; Usein,Filis (2014)
Our study showed that there is a relationship between market share and loyalty. Regarding the relationship between loyalty and price elasticity and price and loyalty, the study shows a very weak correlation. Thus the conclusion that there is no correlation .
Keywords: Priselasticitet; Kundlojalitet; Prisförändringar; Varumärke; Livsmedel; Price elasticity of demand; Customer loyalty; Price changes; Branding; Food